PATTERN OF MEDICATION USE AMONG ELDERLY INPATIENTS IN A TERTIARY CARE HOSPITAL OF NORTHEAST INDIA - DK, BRAHMA; SARKAR, CHAYNA; LAHON, JOONMONI; WAHLANG, JULIE; PK, BHATTACHARYA; KG, LYNRAH; NONGKYNRIH, BANYLLA SHISHA; KUPAR NONGRUM, PYNJOP (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The objective of the present study was to assess the pattern of medication use among elderly inpatients of internal Medicine Wards and to evaluate inappropriate prescribing with the help of Beers criteria 2019. Methods: It was a retrospective hospital data-based study. Data were obtained from treatment charts of elderly inpatients stored in the Medical Records Department. Total 236 treatment record charts of patients ≥60 years of either sex was obtained from the period of July 2015 to December 2015 and the information were noted in predesigned pro forma. Results: The mean±SD age of the patients was 69.07±7.72 years with male preponderance (58.5%). Maximum number of patients were having respiratory disorders (57.6%), followed by kidney diseases (20.8%), cardiovascular diseases (18.6%), and so on. A total of 2683 drugs were prescribed with average number of 10.68±4.74 drugs per prescription. Only 363 formulations were prescribed by their generic names and 29.1% drugs were prescribed as fixed dose combinations. Polypharmacy was seen in 91.5% and 39%, respectively, in hospital stay and during discharge. About 60.5% drugs were prescribed from the National list of essential medicine. Total 57 drugs were found to be potentially inappropriate. About 22% patients received at least one drug which was potentially inappropriate according to Beers criteria and around 14% drugs were prescribed inappropriately. Conclusion: This study suggests that use of potentially inappropriate medications is common in elderly patients, some of them associated with high degree of risk in terms of worsening of the co-morbidity or drug-drug interactions. There is a need for nationwide assessment and strategies that may reduce or overcome such high prevalence.